Quantile-based Study of Interval Inaccuracy Measures - Tehlan, Seema; Kumar, Vikas; Rathee, Anjali (Statistics, Optimization & Information Computing, 2025)
There are many models for which quantile function are available in tractable form, though their distribution functions are not available in explicit form. Recently researchers have great interest to study the quantile-based Interval entropy measures. In the present paper, we introduce quantile-based inaccuracy measure for doubly truncated random variable and study its properties. We also discuss some characterization results of this proposed measure. Further we propose and study the quantile version of Kullback -Leibler divergence measure for doubly truncated random variable. Finally, We discuss some results of proposed Kullback -Leibler divergence measure.